Les acadianismes dans le dictionnaire québécois Usito - Gauvin, Karine (Ponti/Ponts, 2021)
This paper examines the treatment of lexical acadianisms as featured in Usito, a new on-line Québec French dictionary that focuses primarily on standard usage. Unlike other French communities, Acadia does not yet have a dictionary that incorporates its own contemporary usages. The reasons for this are many, the first of which has been a propensity to restrict description of usage to an idealized version of Acadian French as spoken in earlier centuries. Indeed, a review of the main glossaries and dictionaries of Acadian French (Gauvin 2014) has shown that most, if not all, of these works have put forward a single view of Acadian French, ie a more traditional and patrimonial French. To meet its educational needs, the Acadian community has thus far been compelled to consult mostly Paris-based reference works. As the main objective of Usito is to highlight North American content, could it come to replace other, more commonplace dictionaries in Acadia? Our analysis shows that although Usito does project a folkloric viewpoint of Acadian French, the dictionary also showcases other terms that are representative of present practices; these could serve as a springboard to bring about a more thorough study of the Acadian lexicon. Acadie, acadianisme, anglais, canadianisme, dictionnaire, français acadien, lexique, norme, Québec, Usito